Coffe Coffee Seed Waste silage technology as goat feed in Tigapanah Sub-district, Karo regency: Coffee Seed Waste silage technology as goat feed in Tigapanah Sub-district, Karo regency - patriani, peni patriani (Talenta Publisher Universitas Sumatera Utara, 2020)
Coffee is a plantation that produces waste in its processing such as coffee seed waste. Farmers do not know the nutritional content of coffee seed waste is the cause of the waste not being used as animal feed. Coffee bean waste has high water content and caffeine which reduces the cattle's palpability. The solution is to use coffee seed waste silage technology. The method used in community service programs is by approaching, interviewing, exploring problems, and finding solutions to problems. Learning methods using books on how to make silage, providing brochures, banners, and shows that interest farmers. Outputs of this community service program; 1) Increasing the community who use plantation waste as animal feed to reduce feed costs 2) Development of integrated business concepts between livestock and logging. 3) Increased knowledge and skills of farmers 4) Utilization of coffee bean skin waste can reduce environmental pollution. The results that have been obtained are based on observations of the indicators, namely an increase in the number of farmers utilizing coffee fruit husk waste as animal feed, increased knowledge of farmers, increased integrated business cooperation between livestock and plantations, and decreased pollution of environmental waste.